Lifetime Physical Activity, Neuromuscular Performance and Body Composition in Healthy Young Men - Weeda, J.; Horan, S.; Beck, B.; Weeks, B. K. (International Journal of Sports Medicine, 2014)
The purpose of the current study was to determine the relationships between lifetime physical activity participation, neuromuscular performance and body composition in men at musculoskeletal maturity. 50 healthy men (age 25.2±4.5 years) volunteered to participate. Lifetime physical activity was determined from the Bone-specific Physical Activity Questionnaire. Impulse generated during a maximal vertical jump was calculated as an index of neuromuscular performance. Bone mineral density (BMD), lean and fat mass were determined from dual-energy x-ray absorptiometry (XR800, Norland). A subsample of participants (n=13) additionally underwent peripheral quantitative computed tomography (pQCT, XCT3000, Stratec) measures. Results demonstrated that those in the highest tertile for lifetime physical activity exhibited the greatest lumbar spine BMD (µdiff=0.12 g/cm2, p=0.005) and lean body mass index (LBMI) (p=0.04). Those in the highest tertile for impulse also exhibited the highest whole body (µdiff=0.08 g/cm2), lumbar spine (µdiff=0.14 g/cm2), and femoral neck BMD (µdiff=0.15 g/cm2) (p≤0.05). All BMD differences exceeded the least significant change. Childhood physical activity was positively related to LBMI (r=0.28, p=0.05), whereas sedentary activity was inversely related to femoral neck BMD (r=−0.33, p=0.02). Results support recommendations for sustained physical activity participation during the growing years.
Keywords: bone mass; exercise; impulse; lean mass; peripheral quantitative computed tomography